G89(P) Assessment of risk of child sexual exploitation at initial health assessments for looked after children: How well do we do?. (24th May 2017) - Williams, CEP; Stutchbury, J; Bateman, B; Brown, H
Abstract : Aims: Determine how well current Initial Health Assessments (IHA) assess the risk of child sexual exploitation (CSE) in looked after children (LAC) Propose modifications to improve CSE screening Propose methods to improve sexual health promotion Methods: IHA reports (1.2.16–31.8.16) in young persons aged >13 years were reviewed for evidence of sexual health promotion and CSE screening using validated tools: BASHH and Brook guidance 'Spotting the Signs' (StS), and Barnados' modified Child Sexual Exploitation Risk Questionnaire (CSERQ4). A focus group of health professionals who carry out IHAs was held to suggest ways to improve CSE screening. Results: Age demographics (female/male) 13–14 years: 6/0, 15–16 years: 10/6, >17 years:1/1 Asked relationship history=19/24. 15 (79%) in relationship, 11 (58%) sexually active. StS: 7 categories (education, family relationships, friendship, personal relationships, consent, sexual health education, professional analysis). Multiple sub-questions. 0% full compliance. Best performances: Substance use 21 (88%), education history 22 (92%), trusted adult 21 (88%). Particular weaknesses: Confidentiality 0 (0%), self harm 5 (22%), pre-intercourse substance use 2 (18%) STIs 6 (38%), location/nature of intercourse 0 (0%) Focus group (n = 4): Main issues: Time constraints Lack of professional relationship with LAC Intimate questions StS vs: CSERQ: CSERQ4 preferred Conclusion: Current IHA process fails to support screening for CSE using either StS or CSERQ4. Screening for CSE needs to be balanced against other health priorities, developing rapport, and time. Ideally CSE screening should be done by a familiar trusted health professional, but this population is particularly vulnerable, making opportunistic IHA screening appropriate. New 2016 CoramBAAF guidance recommends sexual exploitation risk assessments, but without specifying CSE toolkit. CoramBAAF currently does not fulfil either StS or CSERQ criteria. The focus group recommended integration of CSERQ4, with 'tick box' reminders into the current IHA, with ongoing training. Written information and local signposting on sexual health promotion should be provided.